Hebrew language and grammar (1600)
Unidentified text on Hebrew language and grammar, written ca. 1600-1700 (?) in Latin, with use of Hebrew and Greek. Pages written front and back, apparently in several different hands. The text is a Hebrew grammar made by a Christian. Hebrew texts examined and discussed are biblical. Generally appears to be either a draft of a text never printed, personal notes taken from multiple sources, or perhaps lecture notes. Main text is Latin with significant use of Hebrew and minor use of Greek. -- Bookseller's description